2023
DOI: 10.3390/nu15102334
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of a Ketogenic Diet for Cancer

Abstract: A ketogenic diet has been proposed as a potential supportive therapy for cancer patients, although its long-term influence on survival rates remain controversial. In our previous report, we presented promising results for 37 of 55 patients with advanced cancer enrolled between 2013 and 2018 who remained on a ketogenic diet for at least 3 months. We followed all 55 patients until March 2023 and analyzed the data up to March 2022. For the 37 patients with previously reported promising results, the median follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Although dropout rates were reported by many trials, no study has analyzed the effects of dropout on treatment efficacy. One trial reported that a longer continuation of the KD improved the prognosis of advanced cancer patients, which may support the conclusion that a high dropout rate may dilute the benefits of diet interventions [ 81 ]. However, current evidence is based on secondary analyses, retrospective or observational studies, or preliminary RCTs.…”
Section: Protocol Heterogeneity In Dietary Interventionsmentioning
confidence: 91%
“…Although dropout rates were reported by many trials, no study has analyzed the effects of dropout on treatment efficacy. One trial reported that a longer continuation of the KD improved the prognosis of advanced cancer patients, which may support the conclusion that a high dropout rate may dilute the benefits of diet interventions [ 81 ]. However, current evidence is based on secondary analyses, retrospective or observational studies, or preliminary RCTs.…”
Section: Protocol Heterogeneity In Dietary Interventionsmentioning
confidence: 91%